The police and their image : a comparative study of the American and Cape Town policeman - Albert, Kathleen (1978)
This thesis attempts to understand and compare urban police methods between two fundamentally different legal systems: The United States and South Africa. To do so, I found it imperative to analyze the police systems on three different levels